2006
DOI: 10.32398/cjhp.v4i3.1965
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Mental Health Education Program for South Asian International Students in United States

Abstract: Migration predisposes international students to problems related to mental health. Students from Asia experience a totally different culture when they move to the United States. Within Asia there are several heterogeneous subgroups and one such group is that of South Asians or the students from the Indian Subcontinent that share somewhat similar culture. Often due to achievement of academic success this group is considered a “model minority” group but that is not the case when we see mental health issues. Henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Despite this growing interest, extant research using racially and ethnically diverse participants is limited. This study extends the cross-cultural literature on perfectionism by examining personal and family origins of perfectionism among Asian Indians—an ethnic group that has been largely neglected in Western psychology (Atri & Sharma, 2006; Farver, Narang & Bhadha, 2002; Rahman & Rollock, 2004). This neglect is surprising considering the growing prominence of India.…”
mentioning
confidence: 86%
“…Despite this growing interest, extant research using racially and ethnically diverse participants is limited. This study extends the cross-cultural literature on perfectionism by examining personal and family origins of perfectionism among Asian Indians—an ethnic group that has been largely neglected in Western psychology (Atri & Sharma, 2006; Farver, Narang & Bhadha, 2002; Rahman & Rollock, 2004). This neglect is surprising considering the growing prominence of India.…”
mentioning
confidence: 86%
“…Similar studies could be conducted to understand the actions taken by academic and professional staff to alleviate the challenges faced by students from other regions, such as Latin America, Europe and China. Second, this paper follows Atri and Sharma's (2006) approach of treating students from the Indian subcontinent as a homogeneous group because they share a very similar culture. Still, considering the size and diversity of the Indian subcontinent, such an approach may reflect an oversimplified research design.…”
Section: Discussionmentioning
confidence: 99%
“…Although students are generally informed of the importance of academic integrity, it is not uncommon for international students to intuitively use the learning and integrity approaches from their native culture (Duff & McKinstry, 2007). This approach is particularly evident during stressful times, such as those encountered when international students attempt to adapt to the new culture and learning environment, potentially alongside other factors, such as financial pressures, homesickness, and religious challenges (Atri & Sharma, 2006;Chirkov et al, 2008;O'Reilly et al 2013), or challenges resulting from the students' specific motivation to seek education in the first instance. For example, Birrell's (2019) study of international students suggested their primary purpose for studying in Australia was to seek other visas, and their university study was considered a 'necessary evil', rather than the main focus.…”
Section: Cross-cultural Challenges For Subcontinent Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…One environmental factor that may reduce one's anxiety level is social support. Social support refers to the psychological and material resources provided by social environment to buffer against the stressful events (Atri & Sharma, 2006). Regardless of the type of support source, social support makes one feel loved, cared for, respected, and valued, affecting one's mental health in a positive way (Ao et al., 2020; Zhang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%